Freemasonry and liberal revolution in Spain: The Confederation of Comuneros - Díez Morrás, Francisco Javier (2019)
The Confederation of Comuneros began at the beginning of 1821 in the Masonic lodges and was created by exalted members as a reaction to the moderation of their brethren. Soon it had many members, spreading throughout Spain and uniquely in rural areas. It was equipped with a simpler structure than Freemasonry, adopting a terminology related to the communal revolts of the first quarter of the 16th century. Among its aims was to carry out a liberal revolution. After a first crisis in October 1822 and a split in February 1823, it weakened, becoming irrelevant once Spain’s constitutional system was demolished.